People's Republic of China-Hong Kong Special Administrative Region : Financial Sector Assessment Program-Crisis Management and Bank Resolution Framework-Technical Note. (IMF Staff Country Reports; Country Report ;, 2014)
This Technical Note on Crisis Management and Bank Resolution Framework was prepared in the context of the Financial Sector Assessment Program for the People's Republic of China-Hong Kong Special Administrative Region (HKSAR). Overall, the existing institutional framework facilitates communication and coordination domestically, as well as on a cross-border basis. Information sharing and coordination among domestic regulatory authorities and with the Government is undertaken through a variety of formal mechanisms, which are supported by sound legal bases for the exchange of confidential information. There are complementary structures in place for macro- and micro-prudential supervision that contribute to the prevention and identification of problems in banks. Market-wide or bank intrinsic risk issues will be identified by macroprudential surveillance and bank supervision in the Hong Kong Monetary Authority, or by other financial sector regulatory bodies. The deposit protection scheme is transparent, and trusted; however, steps should be taken to enhance efficiency of pay-outs and to ensure the scheme's sustainability.